Effect of anthocyanin-rich Hungarian tart cherry extract on blood antioxidant status in C57BL/6J mice - Nemes, Andrea; R. Homoki, Judit; Kiss, Rita; Stündl, László; Remenyik, Judit (Acta Agraria Debreceniensis, 2018)
In this study male C57BL/6J (B6) mice were used to determine the possible effects of our Hungarian tart cherry extract in a chronic obesity mouse model on antioxidant capacity. The control group received standard mouse chow, the high fat control group was switched to high fat diet and tap water supplemented with 5% sucrose. The high fat+anthocyanin group received the high fat and sucrose diet, but dissolved in the drinking water they received anthocyanin-rich tart cherry extract. After six weeks, the antioxidant capacity and SOD activity were measured. Antioxidant capacity was decreased with a significant elevation of SOD activity. The tart cherry extract made a significant enhancement in antioxidant capacity and SOD activity. Our results show that chronic anthocyanin intake has a potential to enhance redox status associated with obesity.